2008
DOI: 10.1097/rli.0b013e31816901e2
|View full text |Cite
|
Sign up to set email alerts
|

Lung Perfusion in Patients With Pulmonary Hypertension: Comparison Between MDCT Pulmonary Angiography With minIP Reconstructions and 99mTc-MAA Perfusion Scan

Abstract: MinIP reconstructions can identify different patterns of pulmonary parenchymal attenuation, which show high concordance with perfusion patterns seen on radionuclide studies in patients with pulmonary hypertension. MinIP is a promising technique to evaluate lung perfusion in PH and may be used as an alternative to scintigraphy in the diagnostic work-up of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Such analyses are not infrequently biased by the difficulty of determining an independent criterion standard for the ultimate diagnosis of CTEPH or by the extent of vessel involvement. High-probability V/Q scans or individual perfusion defects in patients are often assumed to be due to CTEPH, although such defects in patients with PH may not be exclusively related to CTEPH (49,53). Traditional research study criterion-standard corroboration with selective pulmonary digital subtraction angiography should also be considered potentially deficient in light of interobserver variability in interpretation and the recognition that many causes of PH may have similar end results on the morphology of peripheral arteries.…”
Section: Perfusion Imaging In Phmentioning
confidence: 99%
“…Such analyses are not infrequently biased by the difficulty of determining an independent criterion standard for the ultimate diagnosis of CTEPH or by the extent of vessel involvement. High-probability V/Q scans or individual perfusion defects in patients are often assumed to be due to CTEPH, although such defects in patients with PH may not be exclusively related to CTEPH (49,53). Traditional research study criterion-standard corroboration with selective pulmonary digital subtraction angiography should also be considered potentially deficient in light of interobserver variability in interpretation and the recognition that many causes of PH may have similar end results on the morphology of peripheral arteries.…”
Section: Perfusion Imaging In Phmentioning
confidence: 99%
“…34 In addition to thromboembolic occlusion in CTEPH, perfusion abnormalities may be caused by parenchymal destruction as in interstitial lung disease and pulmonary emphysema or by distal arteriopathy as in idiopathic PH and other nonembolic forms. 34 Although these different mechanisms produce different perfusion patterns, it is reasonable to hypothesize that measures of overall perfusion would demonstrate lower and more variable parenchymal enhancement in PH compared with normal cases. Indeed, more subtle measurable variations in pulmonary enhancement may be exposed by quantitative PBV imaging as undertaken in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we investigated the feasibility of MDCT angiography in assessing mild to moderate PH in preoperative children in whom it is important to assess pulmonary vascular bed condition for operative indications and postoperative treatment. Bartalena et al first demonstrated that minimum-intensity projection (minIP) reconstructions using MDCT pulmonary angiography could be an alternative to scintigraphy in the analysis of lung perfusion patterns in adult patients [12].…”
Section: Introductionmentioning
confidence: 99%